Why We Play An Anthropological Study - Hamayon, Roberte (HAU Books, 2016)
Whether it's childhood make-believe, the theater, sports, or even market speculation, play is one of humanity's seemingly purest activities: a form of entertainment and leisure and a chance to explore the world and its possibilities in an imagined environment or construct. But as Roberte Hamayon shows in this book, play has implications that go even further than that. Exploring play's many dimensions, she offers an insightful look at why play has become so ubiquitous across human cultures. Hamayon explores facets of play such as learning, interaction, emotion, strategy, luck, and belief, and she emphasizes the crucial ambiguity between fiction and reality that is at the heart of play as a phenomenon. Revealing how consistent and coherent play is, she ultimately shows it as a unique modality of action that serves an invaluable role in the human experience.